Analysis of Skipjack Distribution (Katsuwonus Pelamis) in The Urban Village of West Boepinang Poleang Sub-District Bombana District - Helviani Helviani; Aan Wilhan Juliatmaja (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2017)
This study aimed to identify marketing channels of skipjack; and to know the amount of margin received on each marketing channel of skipjack in the Urban Village of West Boepinang. The research was conducted from May 5 - August 27, 2016 in The Urban Village of West Boepinang, Poleang Sub-District BombanaDistrict. The sample in this research was 37 respondents. Sampling used census method. Data were analyzed using descriptive analysis and marketing margin analysis. The results showed that distribution pattern which is often used by the traders of skipjack commodity in the Urban Village of West Boepinang is the first distribution channel, in which skipjack is distributed from fishermen to merchants to wholesalers to retailers to consumers. Based on profit margin value, wholesalers earned a net profit margin of Rp. 6,972/kg. Similarly, retailers earned a profit margin of Rp. 3,545/kg as well as Rp. 2,793/kg for merchants.